The secretin/secretin receptor axis modulates liver fibrosis through changes in transforming growth factor‐β1 biliary secretion in mice. Issue 3 (11th June 2016) - Wu, Nan; Meng, Fanyin; Invernizzi, Pietro; Bernuzzi, Francesca; Venter, Julie; Standeford, Holly; Onori, Paolo; Marzioni, Marco; Alvaro, Domenico; Franchitto, Antonio; Gaudio, Eugenio; Glaser, Shannon; et al.
Abstract : The secretin/secretin receptor (SR) axis is up‐regulated by proliferating cholangiocytes during cholestasis. Secretin stimulates biliary proliferation by down‐regulation of let‐7a and subsequent up‐regulation of the growth‐promoting factor, nerve growth factor (NGF). It is not known whether the secretin/SR axis plays a role in subepithelial fibrosis observed during cholestasis. Our aim was to determine the role of the secretin/SR axis in activation of biliary fibrosis in animal models and human primary sclerosing cholangitis (PSC). Studies were performed in wild‐type (WT) mice with bile duct ligation (BDL), BDL SR −/− mice, or Mdr2 −/− mouse models of cholestatic liver injury. In selected studies, the SR antagonist (Sec 5‐27) was used to block the secretin/SR axis. Biliary proliferation and fibrosis were evaluated as well as secretion of secretin (by cholangiocytes and S cells), expression of markers of fibrosis, transforming growth factor‐β1 (TGF‐β1), transforming growth factor‐β1 receptor (TGF‐β1R), let‐7a, and downstream expression of NGF. Correlative studies were performed in human control and PSC liver tissue biopsies, serum, and bile. SR antagonist reduced biliary proliferation and hepatic fibrosis in BDL WT and Mdr2 −/− mice. There was decreased expression of let‐7a in BDL and Mdr2 −/− cholangiocytes that was associated with increased NGF expression. Inhibition of let‐7a accelerated liver fibrosis was attributed to cholestasis. There was increased expression of TGF‐β1 and TGF‐β1R. Significantly higher expression of secretin, SR, and TGF‐β1 was observed in PSC patient liver samples compared to healthy controls. In addition, there was higher expression of fibrosis genes and remarkably decreased expression of let‐7a and increased expression of NGF compared to the control. Conclusion : The secretin/SR axis plays a key role in regulating the biliary contribution to cholestasis‐induced hepatic fibrosis. (Hepatology 2016;64:865‐879)